Crustal evolution across the southern Appalachians: Initial results from the SESAME broadband array. Issue 15 (6th August 2013) - Parker, E. Horry; Hawman, Robert B.; Fischer, Karen M.; Wagner, Lara S.
Abstract [1] Receiver functions from the EarthScope Southeastern Suture of the Appalachian Margin Experiment broadband deployment and U.S. Transportable Array were analyzed to constrain average crustal thickness and composition across the southern Appalachians. Low Vp/Vs ratios (1.69–1.72) across the Carolina terrane and parts of the Inner Piedmont indicate that the crust has a felsic average composition. The results are consistent with models of thin‐skinned thrusting of Carolina arc fragments over Laurentian basement, whereas arc collision models require significant crustal modification to explain the low Vp/Vs. New crustal thickness estimates provide constraints on the extent of the Blue Ridge crustal root. The present root may be a remnant of a broader structure formed by Alleghanian thrust loading. Root preservation is attributed to Mesozoic heating and thinning of the lower crust beneath outboard terranes, leaving colder Blue Ridge crust largely intact. However, thickened crust (50–55 km) across the region may also be inherited from continental collision during the Proterozoic Grenville orogeny.